2021
DOI: 10.3390/jmse10010013
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Impact of Building Dimensions on Airflow Patterns and Bed Morphology around Buildings at the Beach

Abstract: The attractiveness of beaches to people has led, in many places, to the construction of buildings at the beach–dune interface. Buildings change the local airflow patterns which, in turn, alter the sediment transport pathways and magnitudes. This induces erosion and deposition patterns around the structures. In this study, a numerical model is developed using the open-source computational fluid dynamics solver OpenFOAM. First, the model is used to predict the airflow patterns around a single rectangular buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Therefore, further research by additional field experiments, controlled wind tunnel experiments, or CFD modelling of airflow around buildings (e.g. Pourteimouri et al, 2022), would be very valuable to further test and develop the theory. For instance, experiments with more repetitions or buildings with various length:width ratios would help to determine if other fractions than the so far used linearly interpolated steered fractions (i.e.…”
Section: Building Orientationmentioning
confidence: 99%
“…Therefore, further research by additional field experiments, controlled wind tunnel experiments, or CFD modelling of airflow around buildings (e.g. Pourteimouri et al, 2022), would be very valuable to further test and develop the theory. For instance, experiments with more repetitions or buildings with various length:width ratios would help to determine if other fractions than the so far used linearly interpolated steered fractions (i.e.…”
Section: Building Orientationmentioning
confidence: 99%
“…The distance over which this surplus decays, and hence the initial deposition tail length, depends on the deposition probability p d . In reality, this deposition is also aided by horizontal flow convergence in the horseshoe vortex tails (Pourteimouri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As wind speed slowly reverts to the undisturbed conditions, the sediment transport capacity decreases, explaining the downwind deposition. Apart from wind speed, the complex 3D flow field also plays a role here, with horizontal convergence promoting deposition in the horseshoe vortex tails (Pourteimouri et al, 2022). Directly adjacent to a building, the accelerated airflow can create scour.…”
Section: Background: Deposition and Erosion Around Buildingsmentioning
confidence: 99%
“…This recirculation was caused by a downward deflection of the flow over the front face of the structure to the ground, where it deflects again, resulting in near-bed flow in the opposite direction of the incoming wind direction. Research from Pourteimouri et al [69] reported that the magnitude of wind velocity steadily increases as the distance increases from the reattachment point until it eventually reaches the undisturbed wind velocity magnitude. Additionally, the findings show that the long building requires a longer distance for the wind to reach the undisturbed wind velocity magnitude.…”
Section: Wind Comfort Analysis Of the Existing Conditionsmentioning
confidence: 99%